Royal Society of Medicine : health encyclopedia : the complete medical reference library in one A-Z volume - Youngson, Robert (Bloomsbury Pub. LondonGB, 2002)
Provides an A-Z of disorders, drugs, medical terms and health-related issues including: AIDS, care of the elderly, passive smoking, STDs, and ultrasound scanning. Identifies the seven ages of life as: the newborn infant, toddler, child up to puberty, adolescent, young adult, middle age, and old age; and provides an overview of common medical problems peculiar to each stage. Advises on first aid procedures for emergencies including cardiac arrest, bleeding, fainting, and drug overdose.